The effect of vegetation height and biomass on the sediment budget of a European saltmarsh. (5th March 2018) - Reef, Ruth; Schuerch, Mark; Christie, Elizabeth K.; Möller, Iris; Spencer, Tom
Abstract: Sediment retention in saltmarshes is often attributed to the presence of vegetation, which enhances accretion by slowing water flow, reduces erosion by attenuating wave energy and increases surface stability through the presence of organic matter. Saltmarsh vegetation morphology varies considerably on a range of spatial and temporal scales, but the effect of different above ground morphologies on sediment retention is not well characterised. Understanding the biophysical interaction between the canopy and sediment trapping in situ is important for improving numerical shoreline models. In a novel field flume study, we measured the effect of vegetation height and biomass on sediment trapping using a mass balance approach. Suspended sediment profilers were placed at both openings of a field flume built across-shore on the seaward boundary of an intertidal saltmarsh in the Dengie Peninsula, UK. Sequential removal of plant material from within the flume resulted in incremental loss of vegetation height and biomass. The difference between the concentration of suspended sediment measured at each profiler was used to determine the sediment budget within the flume. Deposition of material on the plant/soil surfaces within the flume occurred during flood tides, while ebb flow resulted in erosion (to a lesser degree) from the flume area, with a positive sediment budget of on average 6.5 g m −2 tide −1 with no significant relationship between sediment trapping efficiency and canopy morphology. Deposition (and erosion) rates were positively correlated to maximum inundation depth. Our results suggest that during periods of calm conditions, changes to canopy morphology do not result in significant changes in sediment budgets in marshes.